STM/STS study of the density of states and contrast behavior at the boundary between (7х7)N and (8х8) structures in the SiN/Si(111) system - Mansurov, Vladimir; Malin, Timur; Teys, Sergey A.; Atuchin, Victor V.; Milakhin, Denis; Zhuravlev, Konstantin (Crystals)
The origin of the contrast appearing in STM images at the boundary between diverse ordered structures is studied using the example of two structures, (7 × 7)N and (8 × 8), formed in the system of a two-dimensional silicon nitride layer on the Si(111) surface during ammonia nitridation. A significant dependence of the contrast between these structures on the voltage applied to the tunnel gap was found and studied both experimentally and theoretically. Variations in the contrast were quantitatively studied in the range from −3 V to +3 V, and they were studied in more detail for the positive biases on the sample from +1 V to +2.5 V, where the contrast was changed more than 2 times. Within the one-dimensional Wentzel–Kramers–Brillouin (WKB) model for the tunnel current, a comparatively simple procedure is proposed for the correction of the experimental STS-spectra of differential conductivity to identify the adequate (feasible) density of electron states (DOS). It is shown that the (8 × 8) structure DOS corresponds to a graphene-like layer of silicon nitride structure. The proposed correction procedure of the empirical differential conductivity spectra measured by STS will be useful for the quantitative determination of the DOS of new two-dimensional materials and surface structures.